MHD characteristics of compression zone in plasma stream generated by MPC - Chebotarev, V.V.; Cherednychenko, T.N.; Eliseev, D.V.; Garkusha, I.E.; Kozlov, A.N.; Kulik, N.V.; Ladygina, M.S.; Marchenko, A.K.; Morgal, Ya.I.; Petrov, Yu.V.; Solyakov, D.G.; Staltsov, V.V. (Вопросы атомной науки и техники, 2012)
An investigation of local MHD plasma parameters in flow and characterizations of plasma streams, generated by different types of plasma accelerators and magneto-plasma compressors, is one of actual and important from point of view basic plasma dynamics research and plasma applications in different technologies. The present paper devoted to analysis of magneto-hydrodynamic characteristics of the plasma stream generated by the MPC compact geometry. Such important parameters as spatial distributions of electric current and spatial distribution of electromagnetic force in plasma stream, plasma density and velocity in compression zone have been investigated. Исследование локальных МГД параметров плазмы в потоке и характеристик плазменных потоков, генерируемых различными видами плазменных ускорителей и магнито-плазменных компрессоров, является актуальной фундаментальной задачей физики плазмы. Настоящая работа посвящена анализу магнито- гидродинамических характеристик плазменного потока, генерируемого MПК. Были исследованы такие важные параметры, как пространственные распределения электрического тока и электромагнитной силы в плазменном потоке, плотность плазмы и скорость в зоне компрессии. Дослідження локальних МГД параметрів плазми в потоці та характеристик плазмових потоків, що генеруються різними видами плазмових прискорювачів і магніто-плазмових компресорів, є актуальною фундаментальною задачею фізики плазми. Дана робота присвячена аналізу магніто-гідродинамічних характеристик плазмового потоку, який генерується MПК. Були досліджені такі важливі параметри, як просторові розподіли електричного струму та електромагнітної сили в плазмовому потоці, густина плазми та швидкістьу зоні компресії.